(untitled) (CAHIERS MAGELLANES-NS, 2024)
India's traditional healthcare system, Ayurveda, is a rich source of well-documented ancient medical knowledge. While the origins of this knowledge can be traced to the Vedic and post-Vedic periods, it is generally believed that a dedicated branch for healthcare was gradually established approximately between 400 BCE and 200 CE. The reason for the lack of recognition of Ayurveda's substantial contributions in medical history literature could be that these early textbooks were written in Sanskrit, a language not often spoken by the general public, not even in India. In this communication, the discovery of paracentesis has been taken up as a case, and a few important references from the representative Ayurveda compendia that hint at a preliminary understanding of the paracentesis have been reviewed. The central argument of this review is that these contributions from Ayurveda too must be recorded and acknowledged when reviewing the milestones in the history of medicine, as Ayurveda may still be able to influence a number of contemporary scientific fields, if revisited with this spirit.